2021
DOI: 10.1016/j.nmni.2021.100840
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome and description of Mixta mediterraneensis strain Marseille-Q2057T sp.nov., a new bacterium isolated from human healthy skin

Abstract: In 2019, by culturing a skin swab from the hand of a 30-year-old healthy woman using the culturomic method, we isolated the new bacterial strain Marseille-Q2057 T (= CSUR-Q2057). Matrix-assisted desorption–ionization time-of-flight mass spectrometry (MALDI-TOF MS) failed to identify this isolate. Analysis of the 16S rRNA gene and Genome-to-Genome comparison suggested that this taxon belongs to a novel bacterial species within the family Erwiniaceae , phylum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This species cluster was effectively published as "Mixta mediterraneensis" (Boxberger et al, 2021). However, both our phylogenetic analysis and GTDB place this taxon in the genus Pantoea.…”
Section: Pantoea "Mediterraneensis_a" ( a B C D E F )mentioning
confidence: 78%
See 2 more Smart Citations
“…This species cluster was effectively published as "Mixta mediterraneensis" (Boxberger et al, 2021). However, both our phylogenetic analysis and GTDB place this taxon in the genus Pantoea.…”
Section: Pantoea "Mediterraneensis_a" ( a B C D E F )mentioning
confidence: 78%
“…However, both our phylogenetic analysis and GTDB place this taxon in the genus Pantoea. The species cluster currently consists of the genome of a single strain, Marseille-Q2057, which was isolated from the skin swabs of a healthy human (Ndiaye et al, 2019;Boxberger et al, 2021). As stated above, P. "mediterraneensis_A" shares an MRCA with P. bituminis sp.…”
Section: Pantoea "Mediterraneensis_a" ( a B C D E F )mentioning
confidence: 99%
See 1 more Smart Citation
“…We identified the genome as M. mediterraneensis . We then used the original genome of Mixta ( Erwinia ) mediterraneensis (Boxberger et al 2021 ) as a database and mapped the reads again in the same way as above. The reassembled genome and transcriptome were improved using Pilon (Walker et al 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the mite metagenomic DNA samples, we assembled the genome of Erwiniaceae bacteria. The next comparison of the assembled genome revealed that it belongs to Mixta mediterraneensis according to high similarity to M. mediterraneensis strain Marseille-Q2057 T that was previously isolated from skin swabs from the hand of a 30-year-old healthy woman (Boxberger et al 2021 ). We focused on describing interactions between mites and bacterial symbionts using functional metagenomics, meta-transcriptomics, and proteomics.…”
Section: Introductionmentioning
confidence: 99%